1964
DOI: 10.1017/s002531540002467x
|View full text |Cite
|
Sign up to set email alerts
|

Sea Water, the Natural Medium of Phytoplankton II. Trace Metals and Chelation, and General Discussion

Abstract: Assays and mixed culture experiments prove that the supply of chelating substances is frequently the most crucial aspect of phytoplankton nutrition in sea water. Experimental results, theoretical considerations and tentative calculations show that this supply is controlled by the stability of the trace metal chelates and in the sea may be mediated by certain unknown minor components of the dissolved organic matter.The results of Parts I and II are considered together and show how seawater quality is closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1970
1970
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…Johnston (1963Johnston ( , 1964 proposed that certain organic compounds present in seawater in trace quantities may exert an important influence on primary production in marine communities. Barber and Ryther (1969, p. 197) suggested that…”
Section: Complexationmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnston (1963Johnston ( , 1964 proposed that certain organic compounds present in seawater in trace quantities may exert an important influence on primary production in marine communities. Barber and Ryther (1969, p. 197) suggested that…”
Section: Complexationmentioning
confidence: 99%
“…Surface dissolved [Cu] in this area are 0.5-l nM (Bruland 19&O) (Sunda 1988(Sunda -1989. Either or both of these scenarios could result in [Mn2+] : [Cu2+] ratios favorable to growth and reproduction, and they could be among those factors involved in "conditioning" upwelled water (Johnston 1964;Barber and Ryther 1969) Stoecker et al (1986) observed that, for a given [Zn'+], growth rates decreased with increasing [Cu2+]; this trend was apparent for all free [Zn"] tested between lo-lo and lo-l2 M (Fig. IOA).…”
Section: Trace Metal Antagonismsmentioning
confidence: 99%
“…of the cupric ion-selective electrode in solutions containing 1 0 ~M CuS04 at 250C support phytoplankton growth (Johnston, 1963(Johnston, , 1964. Johnston went so far as to say, lithe supply of chelating substances is frequently the most critical aspect of phytoplankton nutrition in seawater".…”
Section: N~ Atömus In Raw and Uv Irradiated Vineyard Sound Seawatermentioning
confidence: 99%
“…For example, Johnston (1964) has demonstrated that either no growth, or only poor growth, can be obtained with diatoms (also dinoflagellates that were part of the natural inocu lum) when chelated trace meta Is are n9t inCluded in the cu Ituring medium. As a result of a large number of cu Ituring experiments, with varying water types collected during different seasons, Johnston concludes that "the supply of chelating substances is frequently the most crucial aspect of phytoplankton nutrition in sea water.…”
Section: mentioning
confidence: 99%